Pemanfaatan Media Sosial Instagram Dinas Komunikasi dan Informatika Pemerintahan Kota Padangsidimpuan dalam Publikasi Informasi - Layla Nirwana Lubis; Sori Monang (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Today's technological developments greatly influence the growth of media, both conventional media and digital media such as social media. Social media now functions as a necessity that cannot be separated from the public. One of the most widely used social media is Instagram. How to use it and Instagram's interesting features make Instagram the most popular social media among the public. Users vary from young people, public figures, to government agencies. Government agencies utilize the capabilities of social media, especially Instagram, as a medium for disseminating public information, one of which is the Padangsidimpuan City Government Communication and Information Agency. Instagram was chosen to be one of the social media that is actively used by the Padangsidimpuan City Government Communications and Information Service. With the account name (@kominfopsp). Instagram is used in the use of Instagram social media as a medium of communication and information. The method used to conduct this research is descriptive qualitative, this method is used because the utilization used cannot be calculated or quantified or calculated based on data but requires further interviews and observations. The results of this research are that the Padangsidimpuan City Government Communication and Informatics Service Agency is considered quite successful in its use as a public communication and information medium, although along the way it requires criticism and suggestions from the public in order to build a better Padangsidimpuan City Government Communication and Informatics Service. Keywords: Instagram Social Media, Communication and Informatics Service, Information Publication